Asymptotic Stability for Block Triangular Maps - Cima, Anna; Gasull, Armengol; Mañosa, Víctor (Sarajevo Journal of Mathematics, 2024)
We prove a result concerning the asymptotic stability and the basin of attraction of fixed points for block triangular maps in R^n. This result is applied to some families of discrete dynamical systems and several types of difference equations.